Interdisciplinary Research Paper: Ambiguities and Inconsistencies in the ‘Prescriptions’ toward Development - Stebek, EN (Mizan law review, 2013)
Ethiopia’s Investment Proclamation states that accelerated economic development and improved living standards of the Ethiopian people are the objectives of investment promotion. Moreover, the 1995 Ethiopian Constitution guarantees “the right to improved living standards and to sustainable development.” This paper deals with the ambiguities and inconsistencies in the path towards achieving one of the expectations enshrined in these laws, i.e., the aspiration to bring about development. It discusses the various notions of development that have influenced Ethiopia’s policies and further examines the challenges thereof in clarity, consistency and effectiveness.